AFIKS TIDAK BAKU DALAM BAHASA INDONESIA RAGAM INFORMAL - Zen, Evynurul Laily (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2011)
This paper discusses the form and meaning of conjunctive relation and how conjunctive relation is translated from source language into target language. The different system of amongst languages  in forming words, sentences or paragraph might  represent  peculiar form and meaning. As a part of element in determining logical meaning, conjunctive relation can be in the  form of conjunction, verb, noun, preposition and implicit. Those forms signal how unity of a text constructed. In translation, the use of conjunctive relation forms frequently make problem for translators since it  is closely related to logical meaning in a text.  In translating text, different meaning between two  languages should be occasionally translated into different form and meaning of the two languages. To understand a text comprehensively, a reader must know the unity of a text. One of the aspects to determine unity of a text in translation is conjunctive relation. The unity of a text can be covered with the conjunctive relation which signal logical relation among clauses, sentences and paragraph, so that in translation cohesiveness of a text is interpreted well both in source text and target text.